Improving The Growth And Adaptation Of The Black Orchid Plantlet (Coelogyne Pandurata Lindl) In Various Growing Media by Giving Plant Extracts as Biostimulants at The Acclimatization Stage - Zulfa Zakiah -; Masnur Turnip (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
One of the most important stages in the process of transferring in vitro cultured seedlings to their natural environment is the acclimatization stage. The acclimatization stage is a critical period in plant propagation. The factors that most influence the growth of in vitro seedlings in the acclimatization process are suitable planting media and the administration of biostimulants. This study aimed to obtain the best planting medium and type of biostimulant for the growth of black orchid plantlets at the acclimatization stage. The study used a completely randomized design with a factorial pattern with two factors, namely first factor: type of growing media with 5 levels of treatment (wood sawdust, coconut coir, cocopeat, rice husk, sugarcane dregs) and second factor: type of biostimulant (without biostimulants; Moringa oleifera extract; Centella Asiatica extract; and Melastoma malabathricum extract). The results showed that the highest percentage of plantlet survival (100%) in the early stages of acclimatization was shown in plantlets grown on wood sawdust and coconut coir media. At the advanced acclimatization stage, the type of biostimulant significantly affected the parameters of survival percentage, tiller height, average number and width of leaves, and average number and length of roots. Optimal planting medium and biostimulant type for advanced acclimatization orchid growth is a single treatment of wood sawdust media with a tiller survival rate (100%), the highest number of leaves (4.65 strands), most roots (8.4 strands).